Common ecology quantifies human insurgency - Bohorquez, J; Gourley, S; Dixon, A; Spagat, M; Johnson, N (2009)
Many collective human activities, including violence, have been shown to exhibit universal patterns1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. The size distributions of casualties both in whole wars from 1816 to 1980 and terrorist attacks have separately been shown to follow approximate power-law distributions6, 7, 9, 10. However, the possibility of universal patterns ranging across wars in the size distribution or timing of within-conflict events has barely been explored. Here we show that the sizes and timing of violent events within different insurgent conflicts exhibit remarkable similarities. We propose a unified model of human insurgency that reproduces these commonalities, and explains conflict-specific variations quantitatively in terms of underlying rules of engagement. Our model treats each insurgent population as an ecology of dynamically evolving, self-organized groups following common decision-making processes. Our model is consistent with several recent hypotheses about modern insurgency18, 19, 20, is robust to many generalizations21, and establishes a quantitative connection between human insurgency, global terrorism10 and ecology13, 14, 15, 16, 17, 22, 23. Its similarity to financial market models24, 25, 26 provides a surprising link between violent and non-violent forms of human behaviour.